Current progress and prospects for G protein-coupled estrogen receptor in triple-negative breast cancer - Zhang, Duo; Chen, Hong; Wang, Jinpeng; Ji, Jiale; Imam, Murshid; Zhang, Zhijie; Yan, Shunchao (Frontiers in Cell and Developmental Biology, 2024)
Triple-negative breast cancer (TNBC) is a biologically and clinically heterogeneous disease. The G protein-coupled estrogen receptor (GPER) plays a crucial role in mediating the effect of estrogen and estrogen-like compounds in TNBC cells. Compared with other subtypes, GPER has a higher expression in TNBC. The GPER mechanisms have been thoroughly characterized and analyzed in estrogen receptor α (ERα) positive breast cancer, but not in TNBC. Our previous work revealed that a higher expression of GPER mRNA indicates a better prognosis for ERα-positive breast cancer; however, its effects in TNBC differ. Whether GPER could serve as a predictive prognostic marker or therapeutic target for TNBC remains unclear. In this review, we provide a detailed introduction to the subcellular localization of GPER, the different effects of various ligands, and the interactions between GPER and closely associated factors in TNBC. We focused on the internal molecular mechanisms specific to TNBC and thoroughly explored the role of GPER in promoting tumor development. We also discussed the interaction of GPER with specific cytokines and chemokines, and the relationship between GPER and immune evasion. Additionally, we discussed the feasibility of using GPER as a therapeutic target in the context of existing studies. This comprehensive review highlights the effects of GPER on TNBC, providing a framework and directions for future research.